Preparing, optimising, and evaluating chitosan nanocapsules to improve the stability of anthocyanins from Aronia melanocarpa. Issue 1 (23rd December 2020) - Wang, Mingyue; Li, Li; Wan, Meizhi; Lin, Yang; Tong, Yuqi; Cui, Yanmin; Deng, Haotian; Tan, Chang; Kong, Yanwen; Meng, Xianjun
Abstract : During in vitro digestion and enviromental storage, the chitosan nanocapsulation was successfully improved the physical and oxidative stability of anthocyanins from Aronia melanocarpa . Abstract : The anthocyanins extracted from Aronia melanocarpa are of great interest because of their potential health-related functionalities. However, their poor stabilities have limited their use in applications. Hence, to improve their physical and oxidative stability, we optimised the chitosan nanocapsules encapsulating anthocyanins from Aronia melanocarpa, and evaluated the systems in terms of their physicochemical characteristics, physical and oxidant stability in simulated gastrointestinal digestion and different storage environments. Results show that the obtained nanocapsules present favorable particle size (197 nm) with good surface morphology, highly encapsulation efficiency (65.7%), suitable zeta potential (+42.7 mV), and low polydispersity index (0.032). Furthermore, compared with free anthocyanins, the nanoencapsulated anthocyanins exhibited significantly slower degradation and stronger antioxidant activity during the simulated gastrointestinal digestion and environmental storage. Thus, the physical and oxidative stability of anthocyanins in Aronia melanocarpa was enhanced significantly by chitosan nanoencapsulation.